Assessing changes in atmospheric circulation due to ecohydrological restoration: how can global climate models help? - Makarieva, Anastassia M.; Nefiodov, Andrei V.; Cuartas, Luz Adriana; Nobre, Antonio Donato; Pasini, Felipe; Andrade, Dayana; Nobre, Paulo (Frontiers in Environmental Science, 2025)
In a steady-state hydrological cycle, terrestrial precipitation is divided into evapotranspiration-a measure of biological productivity-and liquid water runoff. Both processes are crucial to local communities, and ecohydrological restoration should enhance both. Here, based on the law of mass conservation, we show that a necessary condition for runoff to increase alongside evapotranspiration is an increase in precipitation coupled to a change in air circulation. Precipitation is governed by atmospheric dynamics, particularly how quickly moist air rises. Unless these dynamics also intensify, an increase in evapotranspiration, while boosting biological productivity, will simultaneously cause an undesirable decrease in runoff, reducing water availability for people and livestock. Therefore, it is essential to assess how ecohydrological restoration influences atmospheric circulation. Based on theoretical considerations and observations, previous studies have suggested that atmospheric moistening through evapotranspiration can enhance atmospheric moisture convergence, thereby increasing runoff. However, global climate models commonly used for climate guidance may artificially suppress certain positive feedbacks between precipitation and air motion due to the constraints of convective parameterization. A key question is whether such feedbacks exist in the real atmosphere at large scales, even if their amplitudes are weaker than those simulated by current models with convective parameterization turned off. Here, we briefly review the challenges in representing precipitation-air motion feedbacks and outline a research perspective to assess the ability of global climate models to capture these processes and clarify their underlying physics. This could inform large-scale ecohydrological initiatives that are ongoing or planned worldwide and underscore the importance of preserving ecohydrologically resilient ecosystems.